1 Kings 12:1-20 as the interpretation of the relationship between the division of the kingdom of Israel and the Davidicsolomonic era: an opportunity to correct the wrongs of the past - Groenewald, Alphonso, 1969- (University of Pretoria, 2013)
Dissertation (MA (Biblical and Religious Studies))--University of Pretoria, 2008.